(untitled) (Journal of Informatics and Mathematical Sciences, 2018)
Random contractions and Bernoulli selections are recognized as strong analytical tools of probability distributions theory. The paper investigates the distribution of a Bernoulli selection incorporating a stochastic integral and a random contraction. Moreover, the paper establishes a practical interpretation of the formulated Bernoulli selection.